Ideologi di Balik Iklan Komersial Berbahasa Bali - I Nyoman Muliana (Pusat Kajian Bali Universitas Udayana, 2020)
This study aims to reveal the meaning behind verbal, non-verbal sign, and ideological contained in advertisements written in Balinese-language. This study applied a critical descriptive approach. Eleven Balinese-language advertisements are the study data obtained from the field-observation and analyzed qualitatively by using semiotics, semantics and ideology theories. The results showed that the emergence of grammatical adjective category jaen dominated all culinary data used in this study. Jaen (delicious) is a taste to express food culinary production. There are two advertisements that use the word Jaen metaphorically, such as an expression for orgasmic activity in sexual intercourse, which is contextually understandable. Furthermore, certain verbs used are quite varied and contained a different ideology. Based on the sentence structure, all the study samples used simple sentences and an imperative sentence. There is no rhetorical device in the whole advertisements, but the ideology that stands out is to prioritize local content to persuade consumers.